Fatty acid metabolism-related genes are associated with flavor-presenting aldehydes in Chinese local chicken - Yuan, Xiaoya; Cui, Huanxian; Jin, Yuxi; Zhao, Wenjuan; Liu, Xiaojing; Wang, Yongli; Ding, Jiqiang; Liu, Li; Wen, Jie; Zhao, Guiping (Frontiers in Genetics, 2022)
ABSTRACT Aldehydes are primary volatile organic compounds (VOCs) in local Chinese chicken meat and contribute green grass, fatty, citrus, and bitter almond aromas to chicken meat. To understand the genetic basis of these aldehyde VOC aromas, we used approximately 500 Chinese Jingxing Yellow (JXY) chickens to conduct genome-wide association studies (GWAS) on the flavor traits with the data of single nucleotide polymorphisms (SNPs) and insertions and deletions (INDELs). In total, 501 association variants (253 SNPs and 248 INDELs) were found to be suggestively (SNPs: P-value < 2.77e-06 and INDELs: P-value < 3.78e-05) associated with total aldehydes (the sum of nine aldehydes), hexanal, heptanal, benzaldehyde, (E,E)-2,4-nonadienal, octanal, (E)-2-decenal, nonanal, decanal, and octadecanal. Of them, six SNPs and 23 INDELs reached a genome-wide significance level (SNPs: P-value < 1.38e-07 and INDELs: P-value < 1.89e-06). Potential candidate aldehyde genes were functionally annotated for lipid metabolism, especially fatty acid-related pathways and phospholipid-related gene ontology (GO) terms. Moreover, the GWAS analysis of total aldehydes, hexanal, and nonanal generated the most significant signals, and phenotypic content differed between different genotypes at candidate gene-related loci. For total aldehydes and hexanal traits, candidate genes were annotated based on the significant and suggestive variants on chromosomes 3 and 8 with highly polymorphic linkage blocks. The following candidate genes were also identified: GALM, MAP4K3, GPCPD1, RPS6KA2, CRLS1, ASAP1, TRMT6, SDC1, PUM2, ALDH9A1, MGST3, GMEB1, MECR, LDLRAP1, GPAM and ACSL5. We also found that polyunsaturated fatty acids (PUFAs) (C18:2n6c linoleic acid and C18:3n3 linolenic acid) were significantly correlated with total aldehydes, hexanal, and nonanal contents. PUFAs are important aldehyde precursors, and consistently, our results suggested that candidate genes involved in fatty acid pathways and phospholipid GO terms were identified in association loci. This work provides an understanding of the genetic basis of aldehyde formation, which is a key flavor-forming compound.